Impacts of green infrastructure on flood risk perceptions in Hong Kong - KIM, Seung Kyum (Institutional Knowledge at Singapore Management University, 2020)
To better address climate unpredictability, green infrastructure is increasingly deployed alongside gray infrastructure as an alternative strategy for flood risk mitigation. Previous research has not clearly distinguished the flood-mitigation effects of green infrastructure at the local scale due to its complex range of functions including socioeconomic benefits, ecosystem services, and amenity value. Using data on 3768 housing sales from 2009 to 2019 in Hong Kong, we employ a difference-in-differences framework to examine the effect of green infrastructure on perceptions of flood risk mitigation, with housing prices as a proxy for risk perception. We find a positive effect of green infrastructure on the value of nearby housing. The effect does not exist in apartment units on higher floors, however. This vertical discrepancy further suggests that the observed pricing effects are due to green infrastructure’s capacity to reduce perceptions of flood risk. By contrast, properties near conventional gray infrastructure show no evidence of such effects. The results thus provide quantitative evidence that supports the ongoing shift toward green infrastructure as a form of climate change adaptation.